IMPLEMENTASI PENDEKATAN EKONOMI SYARIAH DALAM PENGEMBANGAN SEKTOR PERTANIAN DAN PETERNAKAN DI DESA CIBODAS, KECAMATAN LEMBANG, KABUPATEN BANDUNG BARAT: TINJAUAN EKONOMI DAN SOSIAL - Solihin, Dadin; Bunyamin, Bubun; Aditya M.R.; Purnama, Irman; Rahmawati, Ifa; Setyowardani, Venny (Jurnal Istimā, 2024)
The research was conducted because it was motivated by a real work lecture program, knowing the socio-economic life, understanding, and literacy of the village community. The research examines how the economic order of villagers is viewed from the economic treasures and Islamic law. The purpose of the research is to find out more deeply about the agriculture, animal husbandry, and rural economic sectors. Research methods are carried out qualitatively descriptively, including observation and interviews, as well as comprehensive theoretical reference studies. The results found that local cultural phenomena in the application of the economic system are more obvious, especially in the concept of Ijon business from agricultural products of Cibodas-Lembang Village residents, the view of Sharia economy is similar to the contract of buying and selling greetings. The Ijon system is carried out only based on assistance and urgent conditions. In conclusion, from our findings, villagers do make Ijon transactions, but we provide solutions with the contract Bai' Salam or Istishna'.